PENINGKATAN KEMAMPUAN GURU DALAM MENYUSUN PENELITIAN TINDAKAN KELAS (PTK) MELALUI PENGGUNAAN METODE DISKUSI DI SDN 3 TAMAN FAJAR KECAMATAN PURBOLINGGO - Misrodin; Juwardi; Ari Setyo Gumelar (RETEL Journal (Journal on Publication of The Research on Teaching and Language), 2017)
The purpose of this study is to describe the improvement of the ability of teachers in compiling classroom action research through the use of discussion methods at Taman Fajar State Elementary School 3. This type of research is School Action Research. The model used is a spiral model with research procedures consisting of action planning, action implementation, observation, and reflection. The study was conducted through two cycles of action. Data collection methods used were nontest, test, observation, which was conducted by researchers with colleagues. In analyzing the research data used a qualitative descriptive method which is assisted with the calculation of percentages. Based on the results of the study can be described that the activities of the first cycle after the discussion method used the ability of teachers in preparing Classroom Action Research is not satisfactory. Of the four teacher groups, two groups (50%) had good grades and the other two groups (50%) had poor grades. Cycle I was also unsatisfactory, from 9 teachers as many as 5 people (55.6%) had the ability to understand the preparation of Classroom Action Research individually was good, while 4 people (44.4%) had less ability. The results of the second cycle showed that the ability of teachers experienced a satisfactory increase. From 4 groups of teachers who have the ability to compile Classroom Action Research with a value of> 80 (good) totaling 3 groups (75%), while those with a value of 75 (enough) are 1 group (25%). Individually the teacher's ability to understand how to prepare Classroom Action Research has also been satisfactory. From 9 teachers as many as 7 people (77.8%) have the ability to understand the preparation of Classroom Action Research Classroom Action Research individually is good, while 2 people (22.2%) ability is still lacking. From the results of the above research it can be concluded that the ability of teachers in compiling classroom action research at Sekolag Dasar Negeri 3 Taman Fajar. can be improved through the use of discussion methods.